Design manual for bicycle traffic. - (:unkn) unknown (Crow, 2016)
Encouraging bicycle use is seen as a way to resolve accessibility problems, make a substantial contribution to sustainability targets and offer a healthy and reliable means of transport. This manual will help designers and policymakers to give the bicycle a full-fledged place in the traffic and transport system and offers a wide array of arguments, empirical data, ideas and tips for effective cycling infrastructure and appropriate cycle facilities. The 2006 design manual for bicycle traffic has been fully revised for 2016. The revised edition includes new topics, such as bicycle highways, appropriate cycle paths and roundabouts for cyclists. In addition, extra focus has been given to proven measures and facilities. But facilities cannot be realized without policy. The Design Manual thus pays ample attention to the policy-related aspects of bicycle traffic and supersedes the Policy Manual for Bicycle Traffic issued by the Dutch Bicycle Council (Fietsberaad).
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Fahrradinfrastruktur; Verkehrsplanung; Verkehrssicherheit; Radweg; Radwegenetz; Radverkehrsanlage